IDNLearn.com offers a comprehensive platform for finding and sharing knowledge. Discover detailed answers to your questions with our extensive database of expert knowledge.
Sagot :
Answer and Step-by-step explanation:
|\
| \
| \
| \
| \
| \ 9 + x
x - 9 | \
| \
| \
| \
| \
|_____________\
x
That is your triangle.
Now, since its a right triangle, we can use the Pythagorean theorem to solve for x.
The equation for the Pythagorean theorem is this: [tex]A^{2} + B^{2} = C^{2}[/tex]
So we plug in the values.
[tex](x^{2} ) + (x-9)^{2} = (x + 9)^{2}[/tex]
We solve for x.
[tex]x^{2} + x^{2} -18x + 81 = x^{2} + 18x + 81[/tex]
Get everything to the left side of the equation. (x^2 + x^2 = 2x^2, - x^2 = x^2;
-18x - 18x = -36x; 81 - 81 = 0)
[tex]x^{2} -36x = 0[/tex]
Add 36x to both sides, then divide by x.
[tex]x^{2} = 36x\\\\x = 36[/tex]
Shortest Leg = 36 - 9 = 27
Longest Leg = 36
Hypotenuse = 45
#teamtrees #WAP (Water And Plant)
Thank you for being part of this discussion. Keep exploring, asking questions, and sharing your insights with the community. Together, we can find the best solutions. Thank you for choosing IDNLearn.com. We’re here to provide reliable answers, so please visit us again for more solutions.